Do electoral rules have an effect on electoral behaviour? An impact assessment. Issue 3 (4th May 2017) - Dassonneville, Ruth; Hooghe, Marc; Lewis-Beck, Michael S.
Abstract: Electoral democracies worldwide are all organised around elections but the rules under which the elections are organised differ greatly from one country to another. These electoral rules, such as whether voting is compulsory or what electoral system is used, are thought of as strongly affecting voters' behaviour and the choices they make. If electoral rules indeed shape citizens' electoral behaviour, the implication is that theories of what explains voters' choices are country-specific as well. This is in sharp contrast to the idea that theories of electoral behaviour are generalisable. This special issue tackles this question and offers an assessment of the impact of electoral rules on voters' behaviour, on the one hand, and the generalisability of individual-level theories of voting behaviour, on the other. The collection of papers furthermore offers an important contribution in terms of the kind of electoral rules that are scrutinised, with several papers focusing on the little-investigated phenomenon of preferential voting.